Identifikasi dan Karakterisasi Sumber Daya Genetik Tanaman Buah-buahan Lokal di Kabupaten Gianyar - NI WAYAN PENI YULIAWATI; I WAYAN WIRAATMAJA; HESTIN YUSWANTI (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2016)
Identification and Characterization of Genetic Resources of Local Fruits in GianyarThe local fruits is every kinds of fruits are cultivated and developed by farmers in Bali, while the local fruit products is every types and derivative results which derived from fresh fruits or already processed. This study conducted with the aims to identify the types of genetic resources of local fruits in Gianyar, to compile the genetic resources of the local fruits based on the morphological characters and utilization, superior fruit, harvest seasons and the geographical map of the diversity distribution of the local fruits. This study was conducted in February-July 2015 throughout Sub-district in the Gianyar District, namely: Payangan, Tegallalang, Tampaksiring, Ubud, Blahbatuh, Gianyar and Sukawati. The study consists of three phases, namely; Secondary data collection, field surveys for the types of genetic resources and distribution, and identify of the morphological characters and agronomy, utilization, superior fruit, harvest seasons and the distribution map of the local fruits. The results of this study shown, was found 45 species and 41 sub species of fruits which are spread throughout Sub-districts, and the three of seeded commodities namely; Citrus, Mangoes and Papaya.